PHYTOTOXITY OF NEEM SEED KERNEL EXTRACT AND ITS EFFECTS FOR THE CONTROL OF COWPEA FIELD PESTS IN BAUCHI STATE, NIGERIA - Abdu, A.I.; Aliyu, M.; Shuaibu, Y.M.; Isah, K.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Field trial was conducted during the rainy season of 2024 at Abubakar Tafawa Balewa University, Teaching and Research Farm Bauchi, Gubi campus to investigate the effect of neem seed kernel extract for the control of cowpea insect pests. The treatments consisted of neem seed kernel oil (0.5L/ha, 1L/ha and 1.5L/ha), one cowpea variety obtained from Institute for Agricultural Research, Samaru (Sampea-13), 2%Acetamiprid+1.5%Lamdacyhalothrine EC (1L/ha) and zero application (control). These were combined to give 5 treatments. The result revealed there were significant differences(p≤0.01) between the insecticides on number of aphids per plant, proportion (%) of plants infested by aphids, number of maruca larva per flower, proportion of flowers infested by the larva, number of damaged pods, number of clavigralla per plants, number and percentage of shriveled pods. cowpea treated with either neem seed kernel (1.5L/ha) or 2.5%Acetamiprid+1.5%Lamdacyhalothrine had the lowest number of aphids per plant, while untreated cowpea plants had the highest proportion of plants infested by aphids as well as number of aphid per plant, followed by neem seed kernel (0.5L/ha). cowpea plants treated with 2.5%Acetamiprid+1.5%Lamdacyhalothrine had the lowest percentage of plants infested by aphids, flowers infested by maruca larva, shriveled pods and number of damaged pods followed by neem seed kernel (1.5L/ha). In yield and yield components of cowpea, plants treated with either neem seed kernel (1.5L/ha) or 2.5%Acetamiprid+1.5%Lamdacyhalothrine had the highest number of seeds per pod and highest grain yield (8933.33kg/ha and 909.17kg/ha). Neem seed kernel extract had significantly impacted cowpea yield and insect pest infestation; therefore, it is recommended to treat cowpea with 1.5L/ha of neem seed kernel for the control of cowpea insect pests and higher yield.